Efektivitas Pendekatan Case based learning dalam Pembelajaran IPS - Pratama, Iqbal; Maftuh, Bunyamin; Atauupah, Winda Verawati; Alexander, Loxsi; Dwitarachmi, Fania Hafidza (Edukasi IPS, 2025)
This study aims to determine the effectiveness of using the case-based learning approach in Social Studies instruction. The sample was obtained using a simple random sampling technique. The study was conducted in 2025. The research population consisted of 30 seventh-grade students at SMPN 98 Jakarta in the 2025/2026 academic year, located in South Jakarta, Indonesia. The sampling technique used the Slovin formula to obtain a sample size of 30 seventh-grade students. This research employed an experimental method with a one-group pretest-posttest design. In addition, the researcher used a paired-sample t-test to test the hypothesis and the Shapiro–Wilk test to examine data normality. The results of the independent sample test showed that the two-tailed significance value was 0.000 < 0.05; therefore, based on the decision criteria for the paired-sample t-test, it can be concluded that H0 is rejected and Ha is accepted. The findings indicate that the case-based learning approach in Social Studies instruction has a positive effect on students’ learning outcomes. Moreover, beyond improving achievement, case-based learning also trains critical thinking and enhances student collaboration, as it provides learning experiences that strengthen conceptual understanding, make learning more contextual and participatory, and motivate students to be more engaged and active in the learning process.